2022
DOI: 10.1186/s40168-022-01262-7
|View full text |Cite
|
Sign up to set email alerts
|

The oral microbiome, pancreatic cancer and human diversity in the age of precision medicine

Abstract: Pancreatic cancer is a deadly disease with limited diagnostic and treatment options. Not all populations are affected equally, as disparities exist in pancreatic cancer prevalence, treatment and outcomes. Recently, next-generation sequencing has facilitated a more comprehensive analysis of the human oral microbiome creating opportunity for its application in precision medicine. Oral microbial shifts occur in patients with pancreatic cancer, which may be appreciated years prior to their diagnosis. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 121 publications
0
28
0
1
Order By: Relevance
“…Future risk of PC has been linked to the oral microbiome, specifically increased levels of P. gingivalis and Aggregatibacter actinomycetemcomitans ( A. actinomycetemcomitans ) and decreased relative abundance of Leptotrichia and Fusobacteria , suggesting that it may have an impact on the inflammatory condition by expanding, altering, and regulating the commensal microbiome[ 11 - 13 , 29 ]. It's noteworthy that Leptotrichia species, which are opportunistic pathogenic bacteria, are also frequently discovered in immunosuppressed individuals[ 46 ]. Using direct bacterial DNA analysis from samples of people's saliva taken years before diagnosis, a cohort research found strong associations between two periopathogens, P. gingivalis and A. actinomycetemcomitans , and PC[ 1 , 10 , 43 ].…”
Section: Human Microbiome and Pcmentioning
confidence: 99%
“…Future risk of PC has been linked to the oral microbiome, specifically increased levels of P. gingivalis and Aggregatibacter actinomycetemcomitans ( A. actinomycetemcomitans ) and decreased relative abundance of Leptotrichia and Fusobacteria , suggesting that it may have an impact on the inflammatory condition by expanding, altering, and regulating the commensal microbiome[ 11 - 13 , 29 ]. It's noteworthy that Leptotrichia species, which are opportunistic pathogenic bacteria, are also frequently discovered in immunosuppressed individuals[ 46 ]. Using direct bacterial DNA analysis from samples of people's saliva taken years before diagnosis, a cohort research found strong associations between two periopathogens, P. gingivalis and A. actinomycetemcomitans , and PC[ 1 , 10 , 43 ].…”
Section: Human Microbiome and Pcmentioning
confidence: 99%
“…On the other hand, a multinational study involving saliva from pancreatic cancer cases and controls found a high false positive rate when a Japanese dataset was validated against a Spanish dataset or vice versa, or when the selected biomarker species were validated against saliva of cases and controls from other studies with diseases such as rheumatoid arthritis, colorectal carcinoma or diabetes mellitus [ 21 ]. Paradoxically, different studies identify the same species in oral samples associated with either increased or decreased risk for the same cancer type: e.g., genera Leptotrichia and Streptococcus have been associated with both decreased and increased pancreatic cancer risk [ 22 ].…”
Section: Oral Microbiome and Distant Pathologiesmentioning
confidence: 99%
“…A breakthrough in DNA sequencing occurred in the mid-2000s thanks to next-generation sequencing[ 14 ]. Through gene sequencing, metagenomics, metatranscriptomics, metaproteomics, and metabolomics (the recently introduced “meta-omics” techniques) analysis of strain composition, production of metabolites, and other bacterial activities can be performed[ 15 , 16 ]. Consequently, the significant microbiota impact on human physiology and pathology has been increasingly acknowledged over the years.…”
Section: Cancer Developmentmentioning
confidence: 99%
“…Association between periodontal disease or oral dysbiosis and several kinds of cancers (oral, hematological, digestive tract, prostate, uterus, lung, and breast) has been reported with different strengths of association[ 18 ]. In analyzing this relationship, PanCa has been one of the most studied cancers[ 16 , 18 ]. Porphyromonas gingivalis, Fusobacterium, and Aggregatibacter actinomycetemcomitans in the oral microbiota were related to a higher risk of developing PanCa[ 17 , 19 , 20 ].…”
Section: Cancer Developmentmentioning
confidence: 99%